Respuesta :

Answer:

see explanation

Step-by-step explanation:

x² + 3x + 7 = 5 ( subtract 5 from both sides )

x² + 3x + 2 = 0 ← in standard form

(x + 2)(x + 1) = 0 ← in factored form

Equate each factor to zero and solve for x ( zero product rule )

x + 2 = 0 → x = - 2

x + 1 = 0 ⇒ x = - 1

--------------------------------------------------------------

x² - 2 = - 2x² + 5x ( subtract - 2x² + 5x from both sides )

3x² - 5x - 2 = 0 ← in standard form

(3x + 1)(x - 2) = 0 ← in factored form

Equate each factor to zero and solve for x

3x + 1 = 0 ⇒ 3x = - 1 ⇒ x = - [tex]\frac{1}{3}[/tex]

x - 2 = 0 ⇒ x = 2

------------------------------------------------------------

(x + 3)² + 4x = 0 ← expand left side using FOIL and simplify

x² + 6x + 9 + 4x = 0

x² + 10x + 9 = 0 ← in standard form

(x + 9)(x + 1) = 0 ← in factored form

Equate each factor to zero and solve for x

x + 9 = 0 ⇒ x = - 9

x + 1 = 0 ⇒ x = - 1